2022
DOI: 10.1186/s12245-022-00410-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous lactate levels substitute arterial lactate levels in the emergency department

Abstract: Background Arterial lactate (AL) level is an important predictor of patient prognosis. AL and peripheral venous lactate (PVL) in blood gas analysis have a low concordance rate, and PVL cannot be used as a substitute for AL. However, if the AL range can be predicted from PVL, PVL may be an alternative method for predicting patient prognosis, and the risk of arterial puncture complications with AL may be reduced. This could be a safe and rapid test method. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Exclusion of patients with SpO 2 > 97% resulted in a better correlation between those data [ 26 ]. Studies also revealed that the arterial lactate level and the peripheral venous lactate level are not perfectly identical, but they are strongly correlated with each other [ 27 ]. Furthermore, scientists have found not only the peripheral venous but also central venous pH, bicarbonate, base excess, and lactate values have almost 95% limit of agreement with arterial blood samples [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of patients with SpO 2 > 97% resulted in a better correlation between those data [ 26 ]. Studies also revealed that the arterial lactate level and the peripheral venous lactate level are not perfectly identical, but they are strongly correlated with each other [ 27 ]. Furthermore, scientists have found not only the peripheral venous but also central venous pH, bicarbonate, base excess, and lactate values have almost 95% limit of agreement with arterial blood samples [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Some suggest arterial lactate levels may be slightly higher than venous levels but multiple studies suggest a strong correlation. 37,38 The SEP-1 bundle measures do not differentiate between arterial or venous specimens. 11 The normal lactate level range is 0.6 to 2.2 mmol/L.…”
Section: Details Of the Sep-1 Measurementioning
confidence: 99%
“…Elevated lactate levels in studied cases with certain diseases can be linked to morbidity & mortality. When lactate levels had been greater than four mmol/L in individuals with shock that might not be distinguished based on cause, prognosis had been poor (1).…”
Section: Introductionmentioning
confidence: 99%
“…To determine arterial lactate levels in individuals with severe diseases, blood gas analyses have been repeated. Nevertheless, this testing necessitates catheterization (artery line placement) & arterial puncture, which are invasive procedures that carry risk of consequences (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation